Talent Management in China: A Comparison of Multinational Companies and Stated-owned companies - SHI, YU (2020)
The concept of Talent management is gradually emerging in China which is one of the fastest developing economic entity in the world. There is a war of talent in current market environment, more and more companies are aware of the significance of strategic talent management practice. Because the shortage of the talents will become the most essential challenge for companies’ development in the future. Multinational companies (MNCs) and Stated-owned companies are two typical companies in China, however, their talent management systems and practices are totally different. Previous researches have already showed that how MNCs conduct the talent management program in China, there are few studies to compare the difference between MNCs and Stated-owned companies. Therefore, the aim of this research paper will investigate the similarities and difference of talent management programs between MNCs and Stated- owned companies, examine the challenges of talent management program in each types of company. And how can we draw these findings to improve the talent management practices in China for virous of types of companies. Qualitative research will be conduct in this paper, and primary data will be collected from about 20 respondents in MNCs and Stated-owned companies through semi-structured interviews by video colloquy. Our findings will provide great support to strategic human resource managers that a how to explore an appropriate talent management program for their organization. This suggest that exploring more to make a suitable talent management is a proper strategy for companies to gain competitive advantages and finally become their dynamic capabilities.